Quick‐EXAFS setup at the SuperXAS beamline for in situ X‐ray absorption spectroscopy with 10 ms time resolution. (1st January 2016) - Müller, Oliver; Nachtegaal, Maarten; Just, Justus; Lützenkirchen‐Hecht, Dirk; Frahm, Ronald
Abstract : The quick‐EXAFS (QEXAFS) method adds time resolution to X‐ray absorption spectroscopy (XAS) and allows dynamic structural changes to be followed. A completely new QEXAFS setup consisting of monochromator, detectors and data acquisition system is presented, as installed at the SuperXAS bending‐magnet beamline at the Swiss Light Source (Paul Scherrer Institute, Switzerland). The monochromator uses Si(111) and Si(311) channel‐cut crystals mounted on one crystal stage, and remote exchange allows an energy range from 4.0 keV to 32 keV to be covered. The spectral scan range can be electronically adjusted up to several keV to cover multiple absorption edges in one scan. The determination of the Bragg angle close to the position of the crystals allows high‐accuracy measurements. Absorption spectra can be acquired with fast gridded ionization chambers at oscillation frequencies of up to 50 Hz resulting in a time resolution of 10 ms, using both scan directions of each oscillation period. The carefully developed low‐noise detector system yields high‐quality absorption data. The unique setup allows both state‐of‐the‐art QEXAFS and stable step‐scan operation without the need to exchange whole monochromators. The long‐term stability of the Bragg angle was investigated and absorption spectra of reference materials as well as of a fast chemical reaction demonstrate the overall capabilities of the new setup.